2023
DOI: 10.3390/microorganisms11071727
|View full text |Cite
|
Sign up to set email alerts
|

Studies Using Mutant Strains of Azospirillum brasilense Reveal That Atmospheric Nitrogen Fixation and Auxin Production Are Light Dependent Processes

Abstract: As the use of microbial inoculants in agriculture rises, it becomes important to understand how the environment may influence microbial ability to promote plant growth. This work examines whether there are light dependencies in the biological functions of Azospirillum brasilense, a commercialized prolific grass-root colonizer. Though classically defined as non-phototrophic, A. brasilense possesses photoreceptors that could perceive light conducted through its host’s roots. Here, we examined the light dependenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Although traditionally classified as non-phototrophic, Azospirillum brasilense possesses photoreceptors that allow it to perceive light, and previous studies have suggested its ability to respond to light stimuli [12]. The study by Housh et al [13] explores the light dependencies in the biological functions of A. brasilense, a bacterium commonly used as a microbial inoculant in agriculture. The study investigated the light dependency of atmospheric biological nitrogen fixation (BNF) and auxin biosynthesis, along with related processes such as ATP biosynthesis and iron and manganese uptake.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although traditionally classified as non-phototrophic, Azospirillum brasilense possesses photoreceptors that allow it to perceive light, and previous studies have suggested its ability to respond to light stimuli [12]. The study by Housh et al [13] explores the light dependencies in the biological functions of A. brasilense, a bacterium commonly used as a microbial inoculant in agriculture. The study investigated the light dependency of atmospheric biological nitrogen fixation (BNF) and auxin biosynthesis, along with related processes such as ATP biosynthesis and iron and manganese uptake.…”
mentioning
confidence: 99%
“…Legrifi et al [4] and Bustamante et al [11] provided valuable insights into biocontrol strategies against olive root rot and grapevine trunk diseases, showcasing the potential of specific bacterial strains as environmentally friendly alternatives to chemical fungicides. Housh et al [13] revealed unexpected lightdependent responses in Azospirillum brasilense, challenging conventional classifications and expanding our understanding of microbial behavior. Hernández et al [18] uncovered the hidden diversity of endophytic bacteria in Cuban rice seeds, proposing promising candidates for bio-stimulants aimed at boosting crop growth.…”
mentioning
confidence: 99%